Los barbarismos en la oralidad de la lengua castellana de los moradores del barrio Saguaynuma, parroquia Malacatos, cantón y provincia de Loja. Periodo 2014 – 2015 - Martinez Pacheco , Lisseth Estefania (2018)
In the present thesis work called: The barbarisms in the orality of the Spanish language among the inhabitants of the neighborhood Saguaynuma, parish Malacatos, Loja province and canton; It was proposed as general objective, to determine how these affect the use of orality of the Spanish language of the aforementioned place. To develop the research work were used: the scientific method, descriptive method, synthetic analytical method and deductive inductive method. Likewise the techniques of direct observation, dialogue and documentary were used. It was detected that the inhabitants of the neighborhood Saguaynuma effectively make use of barbarism, so that oral communication in them becomes a little confusing thus affecting the purity of it. So he concludes that improper use of words directly involved in the issuance of the message, and if this is not the correct statement will be distorted and unclear.